A second helping of murder - Wenger, Christine Anne, 1952- (Wenger, Christine Anne, 1952- Comfort food mystery, 2014)
"Trixie Matkowski is warming up to running her family's diner in the small town of Sandy Harbor in upstate New York. But the only thing more demanding than serving up piping-hot comfort food twenty-four hours a day is getting to the bottom of a double homicide.... Trixie fondly remembers summers as a child spent visiting the shores of Lake Ontario. Not much has changed--there are still vinyl booths at the Silver Bullet Diner, families eating home-cooked comfort food, and days of swimming in the lake. But before Trixie can say "Order's up," someone's summer is abruptly cut short. One of the cottage residents is found dead, and Trixie suspects the crime might be linked to an unsolved disappearance in the picturesque town's past. As Trixie works with Deputy Ty Brisco to solve both mysteries, their shocking discoveries will shake up the small town. And when word gets out that she's on the case, Trixie's in trouble--after all, the murderer won't spare her life just because she makes a killer corned beef sandwich" --